Native α-Synuclein, 3-Nitrotyrosine Proteins, and Patterns of Nitro-α-Synuclein-Immunoreactive Inclusions in Saliva and Submandibulary Gland in Parkinson's Disease - Emilio Fernández-Espejo; Fernando Rodríguez de Fonseca; Juan Suárez; Eduardo Tolosa; Dolores Vilas; Iban Aldecoa; Joan Berenguer; Fátima Damas-Hermoso (MDPI AG, 2021)
Background. Salivary α-synuclein (aSyn) and its nitrated form, or 3-nitrotyrosine-α-synuclein (3-NT-αSyn), hold promise as biomarkers for idiopathic Parkinson's disease (IPD). Nitrative stress that is characterized by an excess of 3-nitrotyrosine proteins (3-NT-proteins) has been proposed as a pathogenic mechanism in IPD. The objective is to study the pathological role of native αSyn, 3-NT-αSyn, and 3-NT-proteins in the saliva and submandibulary glands of patients with IPD. Methods. The salivary and serum αSyn and 3-NT-proteins concentration is evaluated with ELISA in patients and controls. Correlations of αSyn and 3-NT-proteins content with clinical features of the disease are examined. Immunohistochemical 3-NT-αSyn expression in submandibulary gland sections is analyzed. Results. (a) Salivary concentration and saliva/serum ratios of native αSyn and 3-NT-proteins are similar in patients and controls; (b) salivary αSyn and 3-NT-proteins do not correlate with any clinical feature; and (c) three patterns of 3-NT-αSyn-positive inclusions are observed on histological sections: rounded "Lewy-type" aggregates of 10-25 µm in diameter, coarse deposits with varied morphology, and spheroid inclusions or bodies of 3-5 µm in diameter. "Lewy-type" and coarse inclusions are observed in the interlobular connective tissue of the gland, and small-sized bodies are located within the cytoplasm of duct cells. "Lewy-type" inclusions are only observed in patients, and the remaining patterns of inclusions are observed in both the patients and controls. Conclusions. The patients' saliva presents a similar concentration of native αSyn and 3-nitrotyrosine-proteins than that of the controls, and no correlations with clinical features are found. These findings preclude the utility of native αSyn in the saliva as a biomarker, and they indicate the absence of nitrative stress in the saliva and serum of patients. As regards nitrated αSyn, "Lewy-type" inclusions expressing 3-NT-αSyn are observed in the patients, not the controls-a novel finding that suggests that a biopsy of the submandibulary gland, if proven safe, could be a useful technique for diagnosing IPD. Finally, to our knowledge, this is also the first description of 3-NT-αSyn-immunoreactive intracytoplasmic bodies in cells that are located outside the nervous system. These intracytoplasmic bodies are present in duct cells of submandibulary gland sections from all subjects regardless of their pathology, and they can represent an aging or involutional change. Further immunostaining studies with different antibodies and larger samples are needed to validate the data.